Unihaz Formulation Herbicide Testing In Various Types Of Weeds - Risvan Anwar; Dicky Wahyudi; Sunarti Sunarti; Eka Suzanna; Djatmiko Djatmiko; Farida Aryani (Jurnal Agroqua: Media Informasi Agronomi dan Budidaya Perairan, 2020)
This experiment aims to determine the effect of the herbicide Unihaz formulation on 30 types of weeds that are dominant in agricultural land. The target weeds consist of 10 types of grass weeds, 10 types of nut weeds and 10 types of broadleaf weeds. The tested weeds were sprayed with a herbicide of Unihaz formulation at a dose of 50 l / ha. The results of the study concluded that the herbicide of formulation Unihaz was effective in controlling the 10 weeds of the types of grass, namely Paspalum cunjugatum, Ischaemum timorence, Chrisopogon aciculatus, Brachiaria pospoloides, Echinochloa crus-galli, Imperata cylindrica, Axonopus compressus, Ischaemum globosa, and Cyrtococum oxyphyum. This herbicide was also effective in controlling the 10 weeds of the nut species, namely Cyperus brevifolius, Cyperus trachysanfos, Fimbristylis globulosa, Scleria sumatrensis, Cyperus aromaticus, Cyperus diformis, Scirpus mucronatus, Rhynchospora crystilis, Cyperus digitarius, and Fimbristylis malaceae. The herbicide of formulation Unihaz effectively controls eight types of broadleaf weeds, namely Urena lobota, Helyotis verticilata, Crassocephalum crapidiodes, Emilia sonchifolia, Asystasia intrusa, Mikania cordata, Hyptis suaveolens, and Borreria alata, and was not very effective in controlling the weeds Clidemia hirta, and Melastoma malabatricum.